Applied Microeconomics for Public Policy Maker - "Trivedi, Prajapati" (New Delhi, 1991)
This book is a guided tour through an economist$1 (Bs workshop, introducing readers to various microeconomics concepts and their utility in analyzing economic problems and finding optimal solutions. However, unlike many textbooks, this book does not present microeconomics as just one thing after another. The choice of topics was guided by one over-riding criterion: whether the concept included in the book is useful for understanding or analyzing economic policies in general, and public policies in particular.s
Keywords: Economics